IKKβ programs to turn on the GADD45α–MKK4–JNK apoptotic cascade specifically via p50 NF-κB in arsenite response - Song, Lun (The Rockefeller University Press, 2006)
Cross talk between NF-κB and c-Jun N-terminal kinases (JNKs) has been implicated in the cell life and death decision under various stresses. Functional suppression of JNK activation by NF-κB has recently been proposed as a key cellular survival mechanism and contributes to cancer cells escaping from apoptosis. We provide a novel scenario of the proapoptotic role of IκB kinase β (IKKβ)–NF-κB, which can act as the activator of the JNK pathway through the induction of GADD45α for triggering MKK4/JNK activation, in response to the stimulation of arsenite, a cancer therapeutic reagent. This effect of IKKβ–NF-κB is dependent on p50 but not the p65/relA NF-κB subunit, which can increase the stability of GADD45α protein through suppressing its ubiquitination and proteasome-dependent degradation. IKKβ–NF-κB can therefore either activate or suppress the JNK cascade and consequently mediate pro- or antiapoptotic effects, depending on the manner of its induction. Furthermore, the NF-κB p50 subunit can exert a novel regulatory function on protein modification independent of the classical NF-κB transcriptional activity.